A new procedure for the fabrication of dissimilar joints through injection of colloidal nanoparticles during friction stir processing: Proof concept for AA6062/PMMA joints. (January 2020) - Aghajani Derazkola, Hamed; Simchi, Abdolreza
Abstract: We present a new semi-solid state procedure for efficient joining of dissimilar materials. The process called fed friction stir processing (FFSP) and works based on in-situ injection of colloidal nanoparticles in the welding line during processing. To present the efficiency of the process, friction stir welding of AA6062 aluminum alloy and poly(methyl methacrylate) (PMMA) through injection of alumina nanoparticles is presented. Microstructural features and mechanical characteristics of the weldments are elaborated. It is shown that in-situ feeding of the alumina nanoparticles during FFSP changes the thermo-mechanical regimes of the bonding zone and decreases the thickness of interaction layer at the interface. Microstructural studies also reveal that more nanoparticles (NP) are accumulated at the bottom part of the polymer/metal interface. Mechanical examinations determine a tensile strength of 60 ± 3 MPa, bending strength of 56 ± 2 MPa, and hardness of 79 ± 0.5 ShoreD. These values are on average 14 %, 20 % and 11 %, higher than the measured values for FSWed AA6062/PMMA joints. Differential scanning calorimetry also reveals that the presence of NP changes the thermal stability of the joints. In-situ injection of colloidal nanoparticles combined with friction stir processing (FSP) opens up new opportunities for the fabrication of dissimilar materials with tailored properties. This procedure not only can be used for efficient joining of polymer/metal sheets, but also it can potentially be employed for in-situ surface modification of different material systems and/or joining of dissimilar materials.